Political Economy of Forest Ecology in Sierra Leone: A focus on the Western Area Peninsular Forest (WAPFoR) - Emerson Abraham Jackson (Postmodern Openings, 2018)
This article addressed historical aspects of the political economy involving sustained forest ecology in Sierra Leone as a whole, with emphasis on the Freetown Peninsula and its surrounding communities. Attention is paid to cultural, social and economic aspects involving forest livelihoods of residents on the Freetown Peninsula and far afield. The term 'Political Economy' is used in this situation to denote the relationship between the economics of people's livelihoods and public policy (in relation to the management of legislative procedures) in ensuring that resources in the forest environment is sustainably managed to cater for the livelihood needs of people in Sierra Leone, while at the same time maintaining a balance in protecting the forest ecosystems. The paper has provided a critical review of the political economy of forest ecology in the country on the basis of scholarly discourses, and its applicability in adapting to the fragile political administrative management Sierra Leone have (and is continuing to) experienced. – – Cet article aborde les aspects historiques de l'économie politique impliquant une écologie forestière durable dans l'ensemble de la Sierra Leone, en mettant l'accent sur la péninsule de Freetown et ses environs. communautés. Une attention particulière est accordée aux aspects culturels, sociaux et économiques impliquant les moyens de subsistance des habitants de la péninsule de Freetown et de loin. Le terme «économie politique» est utilisé dans cette situation pour désigner la relation entre l'économie des moyens de subsistance des populations et la politique publique (en relation avec la gestion des procédures législatives) pour assurer la gestion durable des ressources dans l'environnement forestier. besoins de la population en Sierra Leone, tout en maintenant un équilibre dans la protection de la forêt les écosystèmes. Le document a fourni un examen critique de l'économie politique de l'écologie forestière dans le pays sur la base de discours savants, et son applicabilité dans l'adaptation à la gestion administrative politique fragile de la Sierra Leone (et est continuer à) expérimenté.
Additional information: This is based on the author's extensive literature on natural resource management in Sierra Leone.
Keywords: Q01; Q57; 330; Political Economy; Forest Ecology; Critical Discourse; Sustainability; Sierra Leone